Streptomyces clavuligerus strain selection for clavulanic acid biosynthesis: a study based on culture composition effects and statistical analysis (2018)
The clinical and industrial importance of clavulanic acid (CA) promotes the search for novel strategies to boost productivity at lower costs. In this contribution, the production of CA was evaluated in two reference strains of Streptomyces clavuligerus (Sc), ATCC27064 and DSM41826; the strains were tested in different culture media, using product yields and culture media costs as selection criteria. On average, ScATCC reached a concentration of CA 1.6-fold higher than ScDSM, using the isolated soybean protein (ISP) culture medium. A central composite experimental design was used to optimize the medium, by studying the influence of ISP and K2HPO4 concentration on the production of CA. The maximum CA concentration obtained in this optimized medium was 56 mg·L-1, close to the theoretical optimum. Our results confirm that a culture medium containing a rich carbon source such as glycerol and/or starch provides the best conditions for CA production.